Crystal structure of the Rous sarcoma virus intasome - Yin, Zhiqi (Nature, 2016)
Integration of the reverse-transcribed viral DNA into the host genome is an essential step in the lifecycle of retroviruses. Retrovirus integrase (IN) catalyzes insertions of both ends of the linear viral DNA into a host chromosome (1). IN from HIV-1 and closely related retroviruses share the three-domain organization, consisting of a catalytic core domain flanked by N- and C-terminal domains essential for the concerted integration reaction. Although structures of the tetrameric IN-DNA complexes have been reported for IN from prototype foamy virus (PFV) featuring an additional DNA-binding domain and longer interdomain linkers (2–5), the architecture of a canonical three-domain IN bound to DNA remained elusive. Here we report a crystal structure of the three-domain IN from Rous sarcoma virus (RSV) in complex with viral and target DNAs. The structure shows an octameric assembly of IN, in which a pair of IN dimers engage viral DNA ends for catalysis while another pair of non-catalytic IN dimers bridge between the two viral DNA molecules and help capture target DNA. The individual domains of the eight IN molecules play varying roles to hold the complex together, making an extensive network of protein-DNA and protein-protein contacts that show both conserved and distinct features compared to those observed for PFV IN. Our work highlights diversity of retrovirus intasome assembly and provides insights into the mechanisms of integration by HIV-1 and related retroviruses.